ENHANCED MENEZES-VANESTONE ELLIPTIC CURVES CRYPTOSYSTEM - Sadiq, Ahmed Tariq; Kadhim, Nasreen J (Al-Nahrain Journal of Science, 2009)
The group of the elliptic curve points forms an Abelian group, which is a suitable choice for constructing a good problem similar to Discrete Logarithm Problem. This paper introduces a brief overview of the Menezes-Vanestone Elliptic Curves Cryptosystem (MVECC), and attempts to improve it by suggesting a new variation on MVECC to make encryption more efficient than the original elliptic curves cryptosystems.